Fan curiosity, attachment, and allegiance towards Harimau Malaya football fans / Farah Aimi Mohd Kudzi - Mohd Kudzi, Farah Aimi (2015)
Curiosity can be defined as an important and potential motivator that facilitates human exploratory behaviours and plays an important role in motivating learning (Berlyne, 1954). Therefore, curiosity has been regarded as a key intrinsic motivational drive for facilitating human exploratory behaviours in many domains, such as psychology, education, and sport (Park, Mahony, & Greenwell, 2010). Furthermore, curiosity has been found to be one of the crucial motivators that initially influences human exploratory behaviours in many domains (Park, Mahony, & Yu Kyoum, 2011). Nevertheless, there have been evidently few empirical studies being conducted in exploring the fan curiosity in novel sport. This study attempts to determine the factors of fan curiosity, with two additional variables (attachment and allegiance) in order to have better examination on the curiosity construction in a football setting. Thus, a measurement model that consists of Sport Fan Exploratory Curiosity Scale (SFECS), Sport Fan Specific Curiosity Scale (SFSCS), attachment and allegiance, was developed and tested in this study. Some hypotheses are put forward and tested in a causal-comparative study. To carry out this study, 382 of Harimau Malaya football fans were surveyed during the AFF Suzuki Cup 2013 at the National Stadium Bukit Jalil. The data was collected using the event sampling method and structural equation modelling (SEM) was applied for data analyses and confirmatory factor analysis (CFA) were performed to reliable and validate the questionnaire. For the measurement model, the result showed good model fit, x2 (16) = 52.160, p < 0.001, RMSEA = 0.077, and CFI = 0.983. Result from hypothesis testing proved that the attachment was found as a mediator to the relationship between curiosity and allegiance towards sport fans attendance at the stadium. The further findings offer important elements to sport marketers in order to maintain the crowd of sports fans toward consuming in attending matches at the stadium.